Relación entre el grosor gingival y el ancho de la encía queratinizada para determinar el fenotipo gingival. Revisión bibliográfica - Poma Guaillas, Brayan German (2022)
The term phenotype refers to the appearance of the organ affected by both genetic and environmental factors; for this reason, in the present study, the term gingival phenotype, determined by the gingival thickness and width of the keratinized gingiva, has been used to indicate the morphology of the periodontal soft tissue. There are several techniques to establish the gingival phenotype, but there is still no agreement on which one is the most accurate and reliable. This research aimed to analyze the relationship between gingival thickness and keratinized gingival width to establish the gingival phenotype, to know the most effective method to determine the gingival phenotype, as well as its relationship with gender. It is a bibliographic, descriptive, and comparative study, employing the search of articles in electronic databases such as PubMed, Medline, Google Scholar, Scielo, and Elsevier, taking as reference 25 scientific articles. In this review, a positive correlation of 80% was found between clinical parameters, gingival thickness, and the width of the keratinized gingiva to determine the phenotype. The relationship of the phenotype with gender was 60%, where the male and female gender presented a thick and thin phenotype, respectively. The most effective method to determine the gingival thickness was the trans-gingival probing and the transparency of the probe, while to determine the width of the keratinized gingiva, we used the visual method. We concluded that, in most cases, there is a relationship between gingival thickness and keratinized gingival width, i.e., thick phenotypes have more keratinized gingiva when compared to thin ones